2022
DOI: 10.1038/s41467-022-28121-1
|View full text |Cite
|
Sign up to set email alerts
|

Population structure analysis and laboratory monitoring of Shigella by core-genome multilocus sequence typing

Abstract: The laboratory surveillance of bacillary dysentery is based on a standardised Shigella typing scheme that classifies Shigella strains into four serogroups and more than 50 serotypes on the basis of biochemical tests and lipopolysaccharide O-antigen serotyping. Real-time genomic surveillance of Shigella infections has been implemented in several countries, but without the use of a standardised typing scheme. Here, we study over 4000 reference strains and clinical isolates of Shigella, covering all serotypes, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…The presence or absence of several accessory genes can be used for the assignment of genomes to haplogroups with the Clermont scheme [94, 95], and the haplogroup can also be predicted in silico from genomic assemblies with ClermontTyping [96] or EZClermont [97], both of which are implemented within EnteroBase. However, the Clermont scheme ignores Shigella , which consists of E. coli clades despite its differing genus designation [26,42,43], and makes multiple discrepant assignments according to phylogenetic trees [28]. The Clermont scheme also does not properly handle the entire diversity of species and environmental clades/subspecies within the genus Escherichia [28,58,59,61].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence or absence of several accessory genes can be used for the assignment of genomes to haplogroups with the Clermont scheme [94, 95], and the haplogroup can also be predicted in silico from genomic assemblies with ClermontTyping [96] or EZClermont [97], both of which are implemented within EnteroBase. However, the Clermont scheme ignores Shigella , which consists of E. coli clades despite its differing genus designation [26,42,43], and makes multiple discrepant assignments according to phylogenetic trees [28]. The Clermont scheme also does not properly handle the entire diversity of species and environmental clades/subspecies within the genus Escherichia [28,58,59,61].…”
Section: Resultsmentioning
confidence: 99%
“…HC5 -HC10 clusters with maximal internal pair-wise distances within minimal spanning trees of 5 or 10 alleles, respectively, have been used to identify short-term, single source outbreaks of S. enterica and E. coli/Shigella that extended to multiple European countries [33][34][35][36][37].. Pathogen species can also include higher level clusters, which can correspond to somewhat more distantly related bacterial populations that cause endemic or epidemic disease over longer time periods in one or more countries [38][39][40][41]. EnteroBase HierCC has even been used to classify all Shigella [42], which correspond to discrete Lineages of E. coli [26,43], and to define novel sub-species of S. enterica [44].…”
Section: B) Enterobase and Hierccmentioning
confidence: 99%
See 1 more Smart Citation
“…However, specifically for Shigella subtyping, it has been recently suggested that a cgMLST approach is more robust than wgMLST, since, in contrast with the latter, the former eliminates genes associated with mobile genetic elements [66]. In particular, the EnteroBase cgMLST-based approach has been shown to have potential in routine surveillance and population structure analysis [67]. Similarly, studying pINV, we found that whole plasmid sequences are not informative for measuring phylogenetic distances between these plasmids because differences arising from spontaneous IS-mediated rearrangements do not reflect their evolutionary trajectories (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This is important for predicting the pathogenic profile of the strain or for studying outbreaks. For example, by using the classical typing scheme, Shigella strains are classified into four serogroups and more than 50 serotypes [ 45 ]. However, a recent phylogenomic analysis identified eight distinct phylogenetic clusters.…”
Section: Genome Annotation—inferring Taxonomy Pathogenicity and Antim...mentioning
confidence: 99%